Emerging 2D MXene/Organic Heterostructures for Future Nanodevices. (15th September 2020) - Neupane, Guru Prakash; Yildirim, Tanju; Zhang, Linglong; Lu, Yuerui
Abstract: MXenes are a rapidly growing family of 2D materials. Their unique combination of metallic conductivity, hydrophilicity, and highly charged surfaces endow them with excellent electrochemical performance. Appropriate surface functional groups determine their semiconducting properties. The wide selection of various MXene structures and surface functional groups enable tunable work functions and bandgaps, making them prime candidates for many optoelectronic applications. In addition, the discovery of 2D organic semiconductors having single molecular thickness has also greatly attracted research attention due to their optical, electronic, optoelectronic, and mechatronic properties. Moreover, the formation of MXenes/organic 2D heterostructures enables many interesting phenomena in the 2D quantum limit to be observed. This review aims to increase motivation toward the investigation of newly emerging MXenes, 2D organic materials, and their combinational heterostructures. It overviews recent progress in the fundamental investigations of the optical, electronic, and optoelectronic properties in isolated 2D MXenes and organic materials; then, highlights the major importance of 2D MXene/organic heterostructures for applications in exciton–polariton lasers, light emitting devices, wearable electronics, and spintronic devices. The review aims outlines a future roadmap for 2D MXenes, organic materials, and their heterostructures for advanced nanotechnology applications. Abstract : This review overviews recent progress in the fundamental investigations of the optical, electronic, and optoelectronic properties of isolated 2D MXenes and organic materials and highlights the synthetic protocols and the major importance of 2D MXene/organic heterostructures for future devices applications and platforms. This review outlines a roadmap for 2D MXenes/organic heterostructures for advanced nanotechnology applications.